MARKETING APPROACH IN THE MANAGEMENT OF LIBRARY OF UKRAINE - Rybka, Larisa A. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article discusses ways of obtaining economic independence, stay in the conditions of crisis and competition for survival. All this is even more sharply put before the libraries issue their livelihoods and to society argument of its necessity. The article reveals the concept of library management, library marketing, cites the difference between commercial and non-profit marketing.